Activation of TRPC6 by AngⅡ Induces Podocyte Injury and Participates in Proteinuria of Nephrotic Syndrome - Feng, Ye; Li, Manman; Wang, Yunlai; Yang, Mo; Shi, Gaoxiang; Yin, Dengke; Xuan, Zihua; Xu, Fan (Frontiers in Pharmacology, 2022)
Background: Nephrotic syndrome (NS) is a common glomerular disease, the podocyte injury is the character of the primary NS. Podocytopathy is primarily associated with glomerular proteinuria. Losartan, an angiotensin receptor blocker (ARB), is commonly used in the treatment of NS, and the AngⅡ-TRPC6 signaling axis has been reported to act on podocytes to regulate proteinuria in NS. Therefore, the purpose of this study was to explore the relationship between AngⅡ/TRPC6, podocyte injury and proteinuria based on the adriamycin (ADR) NS rat model. Method: All male rats were divided into three groups: Control group, Model group and ARB group. The rat in the model group were induced by ADR, and the rats in ARB group were received ARB after induction of renal injury for 14 days. The changes in parameters related to renal dysfunction, glomerular and podocytes structure damage, such as AngⅡ, angiotensinⅡ type I receptor (AT1R), TRPC6, CaN, Caspase-3, Nephrin and Podocin, were analyzed, respectively. Furthermore, the kidneys were isolated for transmission electron microscopy (TEM), immunohistochemistry and western blot after sacrifice. In vitro, the murine MPC5 podocytes were used to investigate the regulatory effect of flufenamic acid and SAR7334 on the AngⅡ-TRPC6 signaling axis. Flow cytometry and western blot were conducted to determine the relationship between podocyte injury and AngⅡ/TRPC6. Results: In vivo results showed that NS rats developed massive albuminuria and abnormal renal function, accompanied by abnormally increased the level of AngⅡ, TRPC6, AT1R, CaN, decreased expression of actin molecules in podocytes, extensive fusion of foot processes (FP), loss of glomerular structural integrity, collapse of podocyte structure, and skeletal reorganization. In vitro experiments indicated that both AngⅡand flufenamic acid (the specific agonist of TRPC6) stimulated the expression of TRPC6, AT1R and Caspase-3 in podocytes. The AngⅡreceptor blocker (ARB) losartan and TRPC6 specific inhibitor SAR7334 blocked the overexpression of the above proteins. In addition, SAR7334 also attenuated the degradation of podocyte structural proteins and inhibited the fluorescence intensity of intracellular calcium (Ca2+) and cell apoptosis. Conclusion: The involvement of AngⅡin the occurrence of NS proteinuria may be related to podocyte injury induced by activated TRPC6.